Metodyczne aspekty racjonalizacji kosztów informacji - Sołtys, Danuta; Żaczek, Anna (Methodological Aspects of Information Costs Rationalisations, 2005)
Considering increasing role of information in national economy and private enterprises, rationalization of information costs is growing in fundamentality. In the present article authors presented functional elements of information costs account as instrument to information costs rationalization (methodical aspect).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 413-423